"I can't skip it": does free report improve accuracy in false memories?. Issue 3 (16th March 2021) - Wimmer, Marina C.; Whalley, Ben; Hollins, Timothy J.
ABSTRACT: Strategic monitoring of recognition memory by children and adults was examined using a semantic DRM procedure. Children (7- and 10-year-olds) and adults (overall N = 393) studied lists of semantically related words either incidentally or intentionally and were tested with old items, new items and critical lures to judge as old or new. Participants either made a decision about every item they saw (forced report), or they had the opportunity to withhold answers they were uncertain about (free report). Children were less likely to withhold an answer than adults. However, 7-year-olds were more able to resist false memories when given the opportunity to withhold an answer compared to 10-year-olds or adults. In contrast, adults were unable to improve false memory accuracy. These data suggest that once semantically induced false memories have been encoded they are amenable to strategic monitoring at retrieval in children but not adults.